How can health services strengthen support for children affected by overweight and obesity, and their families? - Anthony Zheng; Michelle Cretikos (Sax Institute, 2019)
More than a quarter of Australian children are above a healthy weight (overweight or obese) and risk significant immediate and future health harms. While childhood overweight and obesity is a complex problem requiring multifaceted solutions, identifying children at risk and preventing these health harms should be a part of good clinical care in all health services. Effective secondary and tertiary prevention is feasible. This paper argues that health services can use serial growth assessment to routinely identify and manage children who are above a healthy weight, just as we might routinely identify and manage hypertension in older patients. We highlight the evidence for the acceptability and effectiveness of family-focused clinical intervention for weight management in children. We also outline system-level changes that health services should consider to enable and support routine clinical identification and management of affected children and their families.